Ion‐Beam‐Induced Chemical Mixing at a Nanocrystalline CeO2–Si Interface. Issue 5 (28th February 2013) - Edmondson, Philip D.; Young, Neil P.; Parish, Chad M.; Moll, Sandra; Namavar, Fereydoon; Weber, William J.; Zhang, Yanwen; Mitchell, T.
<x xml:space="preserve">Abstract</x> Thin films of nanocrystalline ceria deposited onto a silicon substrate have been irradiated with 3 MeV Au+ ions to a total dose of 34 displacements per atom to examine the film/substrate interfacial response upon displacement damage. Under irradiation, a band of contrast is observed to form that grows under further irradiation. Scanning and high‐resolution transmission electron microscopy imaging and analysis suggest that this band of contrast is a cerium silicate phase with an approximate Ce:Si:O composition ratio of 1:1:3 in an amorphous nature. The slightly nonstoichiometric composition arises due to the loss of mobile oxygen within the cerium silicate phase under the current irradiation condition. This nonequilibrium phase is formed as a direct result of ion‐beam‐induced chemical mixing caused by ballistic collisions between the incoming ion and the lattice atoms. This may hold promise in ion beam engineering of cerium silicates for microelectronic applications e.g., the fabrication of blue LEDs.